Cordycepin Increases Nonrapid Eye Movement Sleep via Adenosine Receptors in Rats - Hu, Zhenzhen (Hindawi Publishing Corporation, 2013)
Cordycepin (3′-deoxyadenosine) is a naturally occurring adenosine analogue and one of the bioactive constituents isolated from Cordyceps militaris/Cordyceps sinensis, species of the fungal genus Cordyceps. It has traditionally been a prized Chinese folk medicine for the human well-being. Because of similarity of chemical structure of adenosine, cordycepin has been focused on the diverse effects of the central nervous systems (CNSs), like sleep regulation. Therefore, this study was undertaken to know whether cordycepin increases the natural sleep in rats, and its effect is mediated by adenosine receptors (ARs). Sleep was recorded using electroencephalogram (EEG) for 4 hours after oral administration of cordycepin in rats. Sleep architecture and EEG power spectra were analyzed. Cordycepin reduced sleep-wake cycles and increased nonrapid eye movement (NREM) sleep. Interestingly, cordycepin increased θ (theta) waves power density during NREM sleep. In addition, the protein levels of AR subtypes (A(1), A(2A,) and A(2B)) were increased after the administration of cordycepin, especially in the rat hypothalamus which plays an important role in sleep regulation. Therefore, we suggest that cordycepin increases theta waves power density during NREM sleep via nonspecific AR in rats. In addition, this experiment can provide basic evidence that cordycepin may be helpful for sleep-disturbed subjects.